Colectomy prior to diagnosis of primary sclerosing cholangitis is associated with improved prognosis in a nationwide cohort study of 2594 PSC‐IBD patients. Issue 2 (24th October 2017) - Nordenvall, C.; Olén, O.; Nilsson, P. J.; von Seth, E.; Ekbom, A.; Bottai, M.; Myrelid, P.; Bergquist, A.
Summary: Background: Despite the close relationship between primary sclerosing cholangitis (PSC) and inflammatory bowel disease (IBD), the association between colectomy and the prognosis of PSC remains controversial. Aim: To explore whether colectomy prior to PSC‐diagnosis is associated with transplant‐free survival. Methods: A nationwide cohort study in Sweden including all patients aged 18 to 69 years in whom both PSC and IBD was diagnosed between 1987 and 2014 was undertaken. Each patient was followed from date of both PSC and IBD diagnoses until liver transplantation or death, or 31 December 2014. Patients with colon in situ, and colectomy prior to PSC‐diagnosis were compared. Survival analyses were performed using the Kaplan‐Meier method and multivariable Cox regression models. Results: Of the 2594 PSC‐IBD patients, 205 patients were treated with colectomy before PSC‐diagnosis. During follow‐up, liver transplantations were performed in 327 patients and 509 died. The risk of liver transplantation or death was lower in patients treated with colectomy prior to PSC‐diagnosis (HR 0.71, 95% CI 0.53‐0.95) than in patients with colon in situ. Male gender, longer time between IBD and PSC‐diagnosis and older age were all associated with an increased risk of liver transplantation or death. Colectomy after PSC‐diagnosis was however not associated with an increased risk of liver transplantation or death during long‐term follow‐up. Conclusions: In PSC‐IBD patients, colectomy prior to PSC‐diagnosis is associated with a decreased risk of liver transplantation or death. Abstract : Linked Content This article is linked to Tao and Wang, Sabino and Torres, and Nordenvall and Bergquist papers. To view these articles visithttps://doi.org/10.1111/apt.14439, https://doi.org/10.1111/apt.14418 andhttps://doi.org/10.1111/apt.14368 .